2020
DOI: 10.3390/su12198104
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising Design Fixation and Design Limitation and Quantifying Their Impacts on Resource Use and Carbon Emissions

Abstract: Design for sustainability needs to apply a societal perspective. The purpose of this paper is to combine the concept of design fixation with higher levels of analysis. Design fixation is used to describe a blind adherence to known concepts during the design process. It is used mostly at the micro level of design with the focus on the activities of an individual designer or a group of designers. In this paper, design fixation gets conceptually lifted to the levels of the organisation and the institution. We ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In this sector, Mulder et al [137] underlined the importance of aligning design and its maintenance service to have effective and efficient maintenance process, focusing on how to design industrial equipment, such as rolling stock, and the associated design of its maintenance service. However, capturing and exploiting useful information and knowledge in a systematic manner can be a challenge: designing a PSS including a complex product can experience design fixation [70] in the level of organizational design activity, thereby not exploiting the full potential [232]. Based on a study with the oil industry [225], a suggested strategy was to translating dynamic knowledge from installation and operation into more static forms of products, and to make the knowledge relevant beyond the original context.…”
Section: Challenges With Value Co-creation Involving Other Actorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sector, Mulder et al [137] underlined the importance of aligning design and its maintenance service to have effective and efficient maintenance process, focusing on how to design industrial equipment, such as rolling stock, and the associated design of its maintenance service. However, capturing and exploiting useful information and knowledge in a systematic manner can be a challenge: designing a PSS including a complex product can experience design fixation [70] in the level of organizational design activity, thereby not exploiting the full potential [232]. Based on a study with the oil industry [225], a suggested strategy was to translating dynamic knowledge from installation and operation into more static forms of products, and to make the knowledge relevant beyond the original context.…”
Section: Challenges With Value Co-creation Involving Other Actorsmentioning
confidence: 99%
“…Enlarged design space with a system of systems [199] Avoiding fixations [232] Developing sustainable businesses [78] Defining the right balance of integration of products and services [10] Early decision-making focus and the role of people [17] Reaching a consensus among stakeholders [129] Need for data from multi-source [37] [62] Coordinating multiple disciplines involved [1] Agile approaches required [50] Measuring customer value and budget trade-off [175] Integration of the whole design process [19] Eco-efficient design [28] Upgradability of PSS [74] Focus on value cocreation networks [16] [81] [191] Customers' barriers to derive value [75] [184] System and life cycle thinking [235] Dealing with uncertainty for value creation [114] Value co-creationoriented framework [107] Life cycle thinking [235] Determining service strategy [36] [82] Ensuring market positions and achieving economic success [10]. Role dynamics in provider and customer relationships [167] Estimating the costs of life cycle contracts [35] Measuring environmental impact [127] Optimising sustainability across commercial, environmental and societal targets [194] Design methods considering sustainability [154] [122]…”
Section: Challengesmentioning
confidence: 99%
“…This unexploited potential may be due to something defined as design fixation, which refers to blind adherence to a set of existing concepts. Design fixation limits the output of the conceptual design process (Jansson and Smith 1991) also at the organizational level (Wasserbaur and Sakao 2020).…”
Section: Practical Lessons Learned From Early Pss Design Researchmentioning
confidence: 99%
“…Figure6. Distinction between limitation and fixation from the perspective of designing(Wasserbaur and Sakao 2020) developed from(Sakao and Shimomura 2007) …”
mentioning
confidence: 99%
“…Although such product-level design strategies are vital to reduce potential environmental impacts, these tend to be symptomatic solutions as long as the priority of the manufacturing industry is fixated on the generation of revenue through product sales (Roy, 2000). In order to enhance the environmental sustainability potential of design approaches, it is necessary to extend the level of systems perspective to be applied while also considering and involving a wider range of societal actors in the design process (Ceschin & Gaziulusoy, 2016;Wasserbaur & Sakao, 2020). Moreover, it is necessary to decouple the economic performance of the manufacturing industry from resource use through changes in the design of business models (Roy, 2000;Tukker, 2004).…”
Section: Evolution Of Designing For Environmental Sustainabilitymentioning
confidence: 99%